2017
DOI: 10.11648/j.sjee.20170504.13
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Heavy Metal Pollution and Its Effects in Bangladesh

Abstract: Abstract:Heavy metal, one of the most hazardous pollutant that can pose serious threat to human and environment. The concentrations of metals are increasing at an alarming rate due to boost of unplanned industrialization and urbanization. Though some metals are playing crucial role as micronutrients but the excessive amount exert negative impact at great extent. The existence of toxic heavy metals in the air, water and sediment can cause severe problems to all organisms because of their long persistence nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 76 publications
0
5
0
1
Order By: Relevance
“…Cadmium levels do not also differed significantly in all the sampling sites. Manjushree et al, (2013 Simul-Bhuyan andShafmentaliqul-Islam (2017);Mohammed et al, (2017) obtained similar Cd levels in tannery effluents and treatment efficiency of 33.25%. 0.07mg/L and 0.081mg/L were reported by (Sahuet al, 2007;Amanial, 2015).…”
Section: Resultsmentioning
confidence: 92%
“…Cadmium levels do not also differed significantly in all the sampling sites. Manjushree et al, (2013 Simul-Bhuyan andShafmentaliqul-Islam (2017);Mohammed et al, (2017) obtained similar Cd levels in tannery effluents and treatment efficiency of 33.25%. 0.07mg/L and 0.081mg/L were reported by (Sahuet al, 2007;Amanial, 2015).…”
Section: Resultsmentioning
confidence: 92%
“…The results showed that the soil was significantly enriched with titanium, manganese, zinc, lead, arsenic, iron, strontium and antimony as a result of mineral activity. 50 Salman et al evaluated heavy metal contamination in Arabi farms in Elbor, Egypt. Soil contamination with these metals was calculated using pollution factors, degree of pollution, PLI, environmental risk factor (Er), potential environmental risk index and land accumulation index.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of heavy metals in the aquatic environment is of major concern because of their heavy toxicity, and bio-accumulating tendency in the biota. Pollution by heavy metals is a threat to human life and the entire environment as well as the wetland ecosystem [37][38][39]. Contaminated water is not suitable for household uses and possibly hazardous to many aquatic animals and human health.…”
Section: Effects On the Environment And Human Healthmentioning
confidence: 99%